2019
DOI: 10.1080/1828051x.2019.1593058
|View full text |Cite
|
Sign up to set email alerts
|

Anti-parasitic activity of garlic (Allium sativum) and onion (Allium cepa) juice against crustacean parasite, Lernantropus kroyeri, found on European sea bass (Dicentrarchus labrax)

Abstract: The copepod parasite Lernantropus kroyeri impairs the productivity of European sea bass (Dicentrarchus labrax) culture by leading to a direct infection or as a vector for other disease agents. In current conditions, the parasitic infections in mariculture are usually treated with the chemicals, mainly with the pesticides. However, therapeutic chemical use has potential risks on the overall aquatic environment. Thus, the aquaculture sector needs to find alternative substances to the treatment or prophylaxis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Garlic is known for its wide-spectrum of antimicrobial activity that is attributed to allicin and ajoene, which exert multiple inhibitory effects on thiol-dependent enzymatic systems 104 . Similarly, garlic-based treatments demonstrated to be particularly effective in the fight against monogeneans and other parasites 18,105,106 . Farmed barramundi fed diets containing a garlic extract (50 and 150 mL kg −1 ) for 30 days showed a reduction of Neobenedenia sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Garlic is known for its wide-spectrum of antimicrobial activity that is attributed to allicin and ajoene, which exert multiple inhibitory effects on thiol-dependent enzymatic systems 104 . Similarly, garlic-based treatments demonstrated to be particularly effective in the fight against monogeneans and other parasites 18,105,106 . Farmed barramundi fed diets containing a garlic extract (50 and 150 mL kg −1 ) for 30 days showed a reduction of Neobenedenia sp.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds have a wide range of properties such as antimicrobial 9 , immunostimulant and anti-oxidative activities 10 , 11 , and the ability to enhance intestinal absorption 12 , to improve growth 13 and even to reduce cumulative mortality 11 . The effectiveness of garlic ( Allium sativum ) extract as an immunostimulant, antimicrobial and antiparasitic agent has been demonstrated in several fish species 14 18 ; the inclusion of garlic extract in fish diets is effective against monogenean parasites 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of the plants against the diverse disease agents varies by the characteristics of the plant, indicating the need for more specific research (Trasvino Moreno et al 2017;Hyun Kim et al 2018;Tavares-Dias 2018). Various treatment effects of garlic on some Monogeneans have been studied in various fish species (Fridman et al 2014;Schelkle et al 2017) however, the studies on onion effects in fish parasites are relatively scarce (Yildiz et al 2019). This study provides new information on the antiparasitic activity of onion against G. elegans (Monogenea).…”
Section: Discussionmentioning
confidence: 93%
“…The organosulfur compounds of GO modulate the antioxidant defense system because these compounds regulate the GSH-related antioxidant system, which is the main intracellular antioxidant molecule against oxidative damage (Wu et al, 2001). Previous reports also showed that the organosulfur compounds present in GO may be responsible for the hepatorenal amelioration via their antimicrobial and antiparasitic activities (Yavuzcan Yildiz et al, 2019).…”
Section: Discussionmentioning
confidence: 99%